Exploring the Role of Distance Education in Fostering Equitable University Access for First Generation Students: A phenomenological survey - Priebe, Lisa C.; Ross, Tamra L.; Low, Karl W. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2008)
Using a qualitative study of distance education (DE) learners whose parents have not accessed post-secondary education (PSE), this paper proposes themes for further research in the study of first-generation students (FGS). This survey asked a number of open-ended questions about parental influences on university enrollment, and respondents’ reasons for choosing university in general and DE in particular. Findings were consistent with current research in many areas focusing on debt aversion, lower parental guidance, older starting age, and difficulty separating from familial roles. Differences were noted, including lower parental valuation of PSE and an increased emphasis on non-educational priorities, such as family and work. The limitations of the current study are discussed, as well as suggestions for future FGS research in DE.